2020
DOI: 10.1186/s13068-020-01749-1
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Pichia pastoris with surface-display minicellulosomes for carboxymethyl cellulose hydrolysis and ethanol production

Abstract: Backgrounds: Engineering yeast as a consolidated bioprocessing (CBP) microorganism by surface assembly of cellulosomes has been aggressively utilized for cellulosic ethanol production. However, most of the previous studies focused on Saccharomyces cerevisiae, achieving efficient conversion of phosphoric acid-swollen cellulose (PASC) or microcrystalline cellulose (Avicel) but not carboxymethyl cellulose (CMC) to ethanol, with an average titer below 2 g/L. Results: Harnessing an ultra-high-affinity IM7/CL7 prote… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…The Aga1-Aga2 anchor, initially developed by Boder and Wittrup (1997) , has been used in the expression of several proteins ( Blazic et al, 2013 ; Bertrand et al, 2016 ). Particularly in P. pastoris , SED1p and Pir anchors have shown the highest display efficiencies ( Duquesne et al, 2014 ; Li et al, 2019 ; Dong et al, 2020 ).…”
Section: Strategies To Improve Yeast Surface Displaymentioning
confidence: 99%
“…The Aga1-Aga2 anchor, initially developed by Boder and Wittrup (1997) , has been used in the expression of several proteins ( Blazic et al, 2013 ; Bertrand et al, 2016 ). Particularly in P. pastoris , SED1p and Pir anchors have shown the highest display efficiencies ( Duquesne et al, 2014 ; Li et al, 2019 ; Dong et al, 2020 ).…”
Section: Strategies To Improve Yeast Surface Displaymentioning
confidence: 99%
“…It was found that the strain with scaffolded enzymes had a five-fold increase in NADH productivity than with free enzymes. Pichia pastoris , an emerging yeast cell factory, has been recently engineered to display a mini-cellulosome to convert cellulose to ethanol [ 104 ]. To extend the use of the cellulosome scaffold for more complex enzyme pathways, Li and co-workers have engineered a cellulosome in K. marxianus capable of housing up to 63 enzymes ( Figure 7 B) [ 53 ].…”
Section: Protein Shells and Scaffoldsmentioning
confidence: 99%
“…It was also used to construct a simplified β-cyanobacterial carboxysome, consisting of four shell proteins, by assigning ribosomal binding sites (RBS) of appropriate strengths to the components [ 88 ]. Some synthetic cellulosomes were also constructed using the BioBrick strategy [ 53 , 99 , 104 ]. Major shortcomings of the BioBrick strategy include the creation of RE ligation scars flanking each part at every stage of assembly and that digestion and ligations of parts have to be carried out sequentially.…”
Section: Molecular Tools For Constructing Enzymatic Scaffoldsmentioning
confidence: 99%
“…The thermotolerant Kluyveromyces marxianus was modified to secrete cellulases or to display a cellulosome [115][116][117], however, even with higher temperature processes (37 and 40 • C) the maximum ethanol titer attained with these strains was 3.1 g/L. Pichia pastoris, the most frequently used yeast for heterologous production of proteins, was also modified to display a cellulosome, resulting in the production of 2.5 g/L of ethanol from Avicel [118]. The ethanologenic bacteria Zymomonas mobilis, which is extensively studied for second generation ethanol, was engineered to secrete hydrolytic enzymes and was able to produce 43 g/L and 32 g/L of ethanol from CMC and NaOH-pretreated sugar cane bagasse, respectively [119].…”
Section: Engineering Ethanologenic Microorganisms For Cellulase Productionmentioning
confidence: 99%